Peningkatan Keahlian Bahasa Inggris Guru di Kelas Secara Kontekstual di SMP Islam Manbaul Ulum, Gresik - Tri Yuli Ardiyansah; Prativi Khilyatul Auliya; Riska Widiyanita Batubara (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
In this modern era, teachers are required to be able to master various things to support the teaching-learning process, one of which is the ability to use foreign languages such as English. However, not all teachers are trained in using English during the teaching-learning process. This phenomenon happened at the SMP Islam Manbaul Ulum, Gresik, where there were many teachers who had not mastered the use of English in classroom activities. Therefore, it was necessary to have training to improve English skills for teachers in the classroom contextually. This training was intended so that teachers are familiar and trained in integrating English in the teaching process. This training consisted of 4 stages, namely 1) understanding the material, 2) practice and training, 3) implementation, and 4) evaluation. In stage 1, the teachers received an explanation of the expressions that are commonly used during the teaching process in the classroom. At stage 2, the teachers had the opportunity to practice and practice directly. In stage 3, the teachers implemented to the students what they have learned before. Finally, the evaluation was carried out jointly between the teachers, the principal and the service team. From the results of the evaluation, it was concluded thatthe teacher found it helpful in using English in a contextual manner.